Copper oxide-based photothermal conversion material as well as preparation method and application thereof

The synthesis of copper oxide micron flower/carbon nanotube photothermal conversion materials through microwave hydrothermal method has solved the problem of low energy loss and evaporation rate in seawater desalination, and achieved efficient seawater desalination and wastewater purification. Excellent comprehensive performance.

CN119191332APending Publication Date: 2024-12-27YANBIAN UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411425761.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing photothermal materials have problems of energy loss and low evaporation rates during seawater desalination, and the single photothermal conversion efficiency and structural characteristics of commonly used materials limit their wide application.

Method used

The photothermal conversion material of copper oxide micron flower/carbon nanotubes is synthesized by microwave hydrothermal method, and the synergistic effect of its unique micro-nano hierarchical structure and metal oxide semiconductor/carbon-based composite materials is improved by improving the light absorption rate and evaporation rate. And applied to 3D nested structure solar-driven interface steam system.

Benefits of technology

It achieves efficient seawater desalination, significantly improves evaporation rate, high light absorption rate, good self-cleaning ability and long-term stability, providing a low-cost, pollution-free freshwater resource solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191332A_ABST
    Figure CN119191332A_ABST
Patent Text Reader

Abstract

The invention discloses a copper oxide-based photo-thermal conversion material, a preparation method and application thereof, and belongs to the technical field of photo-thermal materials.According to the method, a copper oxide microflower / carbon nano tube photo-thermal conversion material is synthesized through a microwave hydrothermal method, microflowers are formed by mutually supporting ordered nanosheets, and carbon nano tubes are wound on the nanosheets; the refraction and reflection times of incident light in the material can be increased by utilizing a light trap formed by the staggered micro-nano hierarchical structure, so that multiple absorption of sunlight is effectively promoted, and light capture is increased. Meanwhile, through the synergistic photo-thermal effect of the metal oxide semiconductor / carbon-based composite material, the evaporation rate and the light absorptivity can be improved. In addition, the composite photo-thermal material is applied to a 3D nested structure solar driving interface steam system, and continuous and efficient seawater desalination is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal materials, and specifically relates to a copper oxide-based photothermal conversion material, a preparation method and an application thereof. Background Art

[0002] In the context of the increasing scarcity of fresh water worldwide, scientific desalination of seawater, which is widely distributed and abundant in resources, has become a feasible solution to the problem of scarce fresh water resources. Traditional seawater desalination technologies mainly include reverse osmosis membranes, multi-effect distillation, multi-stage flash evaporation, and electro-osmosis. However, these technologies not only require complex basic equipment and high cost investment, but also consume a large amount of fossil fuels during operation, causing environmental pollution. Therefore, it is of great significance to develop a new low-cost, pollution-free water treatment technology that uses clean energy.

[0003] As we all know, solar energy has huge reserves and is green and environmentally friendly, showing good application prospects in the fields of light-heat, light-electricity and light-chemical conversion. Therefore, solar-driven steam technology, which uses solar energy as the only energy input, converts solar radiation energy into heat energy through photothermal conversion materials, promotes water evaporation and collects it, is considered to be an effective strategy to alleviate the shortage of freshwater resources in a forward-looking manner.

[0004] According to the location of the photothermal material in the water body, the solar-driven steam system can be divided into three types: bottom heating evaporation, nanoparticle suspension evaporation and interface evaporation. The first two technologies require heating the entire water body, which inevitably causes energy loss and reduces the evaporation rate. In contrast, the solar interface evaporation system can concentrate the heat generated by sunlight at the gas-liquid interface, thereby significantly increasing the vaporization rate. As the core component of an efficient solar-driven interface steam system, it is crucial to synthesize photothermal conversion materials with excellent light absorption capacity and good chemical stability. Currently, commonly used photothermal materials include plasma metals (precious metals such as gold, silver, and platinum), organic polymers (polypyrrole, polydopamine, and polyaniline, etc.), carbon-based (graphene, carbon nanotubes, and carbonized biomass, etc.) and semiconductor (MoS2, TiO2, and Si, etc.) materials, etc. However, the limited photothermal conversion efficiency of a single material and its inherent structural characteristics restrict its widespread application. Summary of the invention

[0005] In view of the above-mentioned defects existing in the prior art, the present invention provides a copper oxide-based photothermal conversion material, a preparation method and its application. The present invention synthesizes a copper oxide micro-flower / carbon nanotube photothermal conversion material by a microwave hydrothermal method. The micro-flower is composed of orderly arranged nanosheets supporting each other, and the carbon nanotubes are wound on the nanosheets. The light trap formed by the interlaced micro-nano hierarchical structure of the two can increase the number of refractions and reflections of the incident light inside the material, thereby effectively promoting the multiple absorption of sunlight and increasing the capture of light. At the same time, through the synergistic photothermal effect of metal oxide semiconductor / carbon-based composite materials, the evaporation rate and light absorption rate can be improved. In addition, the present invention applies the above-mentioned composite photothermal material to a 3D nested structure solar-driven interface steam system to achieve continuous and efficient seawater desalination.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a copper oxide-based photothermal conversion material, which specifically comprises the following steps:

[0008] Step 1: dissolve copper salt in deionized water, add quaternary ammonium salt cationic surfactant, and stir to form a uniform microemulsion;

[0009] Step 2: Add concentrated ammonia water to the microemulsion synthesized in step 1 by using a constant pressure titration device, perform ultrasonication until the mixture is uniformly mixed, and then heat the mixture in an oil bath and raise the temperature to T1 under stirring;

[0010] Step 3: injecting a strong alkaline solution into the solution synthesized in step 2 using a peristaltic pump, and continuously stirring until the pH is 9-12 to generate a blue copper hydroxide solution Q1;

[0011] Step 4: dispersing carbon nanotubes and polyvinyl pyrrolidone in deionized water to form solution Q2, adjusting the type, size and ratio of carbon nanotubes, uniformly mixing solution Q1 and solution Q2, and transferring them to a microwave reactor for microwave hydrothermal reaction, heating the temperature to T2 for continuous reaction, and cooling to room temperature after the reaction is completed;

[0012] Step 5: Use anhydrous ethanol and deionized water to wash by centrifugation three times, dry at 80°C for 24 hours, and finally obtain the copper oxide-based photothermal conversion material.

[0013] Furthermore, in step 1, the copper salt is one or more of copper nitrate, copper sulfate, copper chloride, copper acetate, copper carbonate, etc.;

[0014] The quaternary ammonium salt type cationic surfactant is one or more of tetraoctylammonium bromide, methyltriethylammonium chloride, dodecyltrimethylammonium chloride and trimethyldecylammonium bromide.

[0015] Furthermore, in step 1, the molar ratio of the copper salt and the quaternary ammonium salt type cationic surfactant is 8:1-12:1.

[0016] Furthermore, in step 2, the concentration of the concentrated ammonia water is 25-28wt%, and the volume is 2-10ml.

[0017] Furthermore, in step three, the strong alkaline solution is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, and barium hydroxide; and the concentration of the strong alkaline solution is 1-3 mol / L.

[0018] Furthermore, in step 4, the mass ratio of the copper salt, the carbon nanotubes and the polyvinyl pyrrolidone is 5:1:1-15:1:1;

[0019] The carbon nanotubes are one or more of conventional multi-walled carbon nanotubes, hydroxylated carbon nanotubes, carboxylated carbon nanotubes, and amino carbon nanotubes; the size of the carbon nanotubes is one or more of 0.5-2 μm, 10-30 μm, and 50 μm.

[0020] Furthermore, the T1 is 50-80° C., the T2 is 120-240° C., and the reaction time is 0.5-6 h.

[0021] In a second aspect, the present invention further provides a copper oxide-based photothermal conversion material, which is prepared by the preparation method described in the first aspect of the present invention.

[0022] In the third aspect, the present invention also provides an application of a copper oxide-based photothermal conversion material in a 3D nested structure solar-driven interface steam system, wherein the 3D nested structure solar-driven interface steam system comprises a water storage unit, a thermal insulation unit and a photothermal conversion unit; the thermal insulation unit is placed above the water storage unit, and the photothermal conversion unit passes through the thermal insulation unit to connect the water body and the air to form a 3D nested structure.

[0023] Furthermore, the water storage unit is a 50 ml beaker filled with simulated seawater; the heat insulation unit is equal to the diameter of the beaker and has a 1×1 cm 2 Square through hole, disc-shaped polyethylene foam with a thickness of 1-2 cm;

[0024] The photothermal conversion unit is to uniformly disperse the copper oxide-based photothermal conversion material in water at a concentration of 30 mg / ml, then inject 3-10 ml into the interior of a foam having a three-dimensional interconnected porous network structure, and dry at 60°C for 10 hours; the foam is one or more of polyurethane foam, melamine foam, polyethylene foam, ethylene-vinyl acetate copolymer foam, and polyimide foam; the foam size is 1×1×3 cm 3 .

[0025] Compared with the prior art, the advantages of the present invention are as follows:

[0026] (1) The copper oxide-based photothermal conversion material prepared by the present invention has a copper oxide micro-flower structure and has intrinsic defects. The generation of defect energy levels makes it easier for photogenerated electrons to transition to the conduction band, thereby gaining an advantage in the field of light absorption; in addition, the larger specific surface area can provide more active sites, which can greatly improve the photothermal conversion capacity. Multi-walled carbon nanotubes have photostability and chemical stability. The presence of conjugated π bonds reduces the energy gap between the highest occupied molecular orbital and the lowest unoccupied molecular orbital; the reduction of the energy gap leads to a red shift in the absorption spectrum, thereby maintaining a high light absorption performance for a long time;

[0027] (2) The unique micro-nano hierarchical structure of 1D multi-walled carbon nanotubes and 3D copper oxide microflowers forms a light trap, which effectively increases the number of refractions and reflections of incident light inside the material, thereby effectively promoting multiple absorptions of sunlight and facilitating the capture of light. At the same time, the synergistic photothermal conversion effect of metal oxide semiconductors and carbon-based materials can effectively broaden the absorption range of the photothermal layer and localize the converted heat on the surface of the material, achieving high-speed solar water evaporation;

[0028] (3) The copper oxide-based photothermal conversion material preferably prepared by the present invention can be applied to the solar-driven interface steam system, and exhibits excellent comprehensive performance in the fields of seawater desalination and wastewater purification. When irradiated with 1 sun, under simulated seawater conditions, the evaporation rate of the interface steam system reaches 4.2521 kg·m -2 ·h -1 The average light absorption rate in the ultraviolet and visible regions is as high as 98%. The copper oxide micro-flower / carbon nanotube photothermal conversion material has excellent evaporation performance, good self-cleaning ability and outstanding long-term stability, providing a new way to alleviate the shortage of fresh water resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0030] Figure 1 Schematic diagram of 3D nested structure solar-driven interface steam system;

[0031] Figure 2 is a light absorption spectrum of the copper oxide / carbon nanotube composite material described in Example 1;

[0032] Figure 3This is a schematic diagram of the long-term stability test of the steam system described in Example 1;

[0033] Figure 4 This is a graph showing changes in concentrations of various metal ions in seawater before and after purification by the steam system in Example 1;

[0034] Figure 5 is a scanning electron microscope image of the copper oxide / carbon nanotube composite material described in Example 1;

[0035] Figure 6 This is a scanning electron microscope image of the copper oxide / carbon nanotube composite material described in Example 2. DETAILED DESCRIPTION

[0036] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:

[0037] Example 1

[0038] This embodiment provides a method for preparing a copper oxide-based light-to-heat conversion material, comprising the following steps:

[0039] Dissolve 0.01 mol of copper sulfate in a 100 ml three-necked flask containing 50 ml of deionized water, add 0.00125 mol of tetraoctylammonium bromide, and stir at 500 rpm until the emulsion is uniform. Add 8.4 ml of ammonia water using a constant pressure titration device, and then ultrasonicate for 5 minutes and oil bath at 70 ° C. Inject 1.5 mol / L of sodium hydroxide solution through a peristaltic pump until the pH of the solution is 10 to obtain solution Q1. Disperse 0.15 g of 10-30 μm hydroxylated multi-walled carbon nanotubes and 0.15 g of polyvinyl pyrrolidone in 30 ml of deionized water, and ultrasonicate and stir for 30 minutes to obtain solution Q2. Mix solutions Q1 and Q2 evenly, transfer to a microwave reactor, program the temperature to 180 ° C, and continue the reaction for 4 hours. After the reaction is completed, cool to room temperature, wash with anhydrous ethanol and deionized water by centrifugation 3 times, and dry at 80 ° C for 24 hours to obtain a copper oxide / carbon nanotube composite material.

[0040] The preparation steps of the 3D nested structure solar-driven interfacial steam system are as follows:

[0041] Prepare a 100 ml beaker containing 50 ml of NaCl solution to simulate seawater. Cut the polyethylene foam into a piece with the same diameter as the beaker and a 1×1 cm 2 The copper oxide / carbon nanotube composite photothermal material was evenly dispersed in water at a concentration of 30 mg / ml, and then 10 ml was injected into the melamine foam (1×1×3 cm) with a three-dimensional interconnected porous network structure. 3) and dried at 60℃ for 10h. Then pass it through the polyethylene foam to form a nested structure. At this time, the part of the melamine foam cube exposed in the air layer (1×1×0.5cm 3 ) is used as the absorption layer of the device, responsible for receiving the radiation of sunlight; the part in contact with the water body is used as the hydrophilic vertical water transfer channel of the device, completing the transfer of water from the water body to the evaporation surface under solar radiation, such as Figure 1 The 3D nested solar-driven interfacial steam system was placed in a closed environment for testing. Under 1 sun irradiation, the evaporation rate reached 4.2521 kg·m -2 ·h -1 The average absorbance in the ultraviolet and visible light regions is 98%.

[0042] In 1×1cm 2 The surface of copper oxide / carbon nanotube composite material is covered with NaCl. -2 The self-cleaning ability test was carried out under the lighting conditions of Figure 2 As shown; the results show that the evaporator has good self-cleaning ability, has obvious dissolution behavior within 60s, and can dissolve a large amount of salt crystals within 300s to avoid their accumulation and clogging of the pores.

[0043] At 1kW·m -2 The stability test was carried out under the lighting conditions of 21 days, with 60 minutes of irradiation per day. Figure 3 As shown, the evaporator can still maintain stable evaporation after long-term operation.

[0044] Seawater samples were collected and the metal ion concentration in the condensed liquid was tested, e.g. Figure 4 As shown; after purification Na + , Ca 2+ , K + Mg 2+ The concentration dropped by 3-4 orders of magnitude, from 10780, 410, 400 and 1298 ppm to 2.082, 0.433, 0.326 and 0.019 ppm respectively. The content of metal ions was far below the upper limit of drinking water standards set by the World Health Organization (WHO).

[0045] By characterizing the microstructure of copper oxide / carbon nanotube composites, such as Figure 5 As shown in the figure, it can be seen that the three-dimensional layered micron flowers are compact inside, and there are nano cavities between the two-dimensional petals, which is conducive to enhancing the light capture ability inside the material. The 1D carbon nanotubes are attached to the surface of the 3D copper oxide micron flowers with their unique tubular structure. The light traps formed by the interlacing of the two can increase the number of refractions and reflections of the incident light inside the material, thereby effectively promoting the multiple absorption of sunlight.

[0046] Example 2

[0047] This embodiment provides a method for preparing a copper oxide-based light-to-heat conversion material, comprising the following steps:

[0048] Dissolve 0.02 mol of copper chloride in a 100 ml three-necked flask containing 50 ml of deionized water, add 0.002 mol of dodecyl trimethyl ammonium chloride, and stir at 600 rpm until the emulsion is uniform. Add 8 ml of ammonia water using a constant pressure titration device, and then ultrasonicate for 5 minutes in an oil bath at 50 ° C. Inject 1 mol / L of potassium hydroxide solution through a peristaltic pump until the pH of the solution is 11 to obtain solution Q1. Disperse 0.2 g, 0.5-2 μm carboxylated multi-walled carbon nanotubes and 0.2 g of polyvinyl pyrrolidone in 30 ml of deionized water, and ultrasonicate and stir for 30 minutes to obtain solution Q2. Mix solutions Q1 and Q2 evenly, transfer to a microwave reactor, program the temperature to 120 ° C, and continue the reaction for 2 hours. After the reaction is completed, cool to room temperature, centrifuge and wash 3 times with anhydrous ethanol and deionized water, and dry at 80 ° C for 24 hours to obtain a copper oxide / carbon nanotube composite material.

[0049] The preparation steps of the 3D nested solar-driven interfacial steam system are basically the same as those in Example 1, except that the copper oxide / carbon nanotube composite material prepared above is loaded on polyurethane foam. Under 1 sun irradiation, the evaporation rate is 3.3861 kg·m -2 ·h -1 The average absorbance in the UV and visible regions is 87%. It can achieve long-term stable brine treatment without any salt deposition and scaling.

[0050] By characterizing the microstructure of copper oxide / carbon nanotube composites, such as Figure 6 As shown in the figure, short and thick carbon nanotubes have a small degree of entanglement and tend to entangle themselves and agglomerate. The occurrence of this agglomeration phenomenon will weaken the material's absorption of light.

[0051] Example 3

[0052] This embodiment provides a method for preparing a copper oxide-based light-to-heat conversion material, comprising the following steps:

[0053] Dissolve 0.03 mol of copper acetate in a 100 ml three-necked flask containing 50 ml of deionized water, add 0.0025 mol of methyltriethylammonium chloride, and stir at 600 rpm until the emulsion is uniform. Add 10 ml of ammonia water using a constant pressure titration device, and then oil bath at 80 ° C after ultrasonication for 5 minutes. Inject 1 mol / L of sodium hydroxide solution through a peristaltic pump until the pH of the solution is 11 to obtain solution Q1. Disperse 0.3 g of 50 μm amino carbon nanotubes and 0.3 g of polyvinyl pyrrolidone in 30 ml of deionized water, and ultrasonicate and stir for 30 minutes to obtain solution Q2. Mix solutions Q1 and Q2 evenly, transfer to a microwave reactor, program the temperature to 200 ° C, and continue the reaction for 4 hours. After the reaction is completed, cool to room temperature, centrifuge and wash 3 times with anhydrous ethanol and deionized water, and dry at 80 ° C for 24 hours to obtain a copper oxide / carbon nanotube composite material. The preparation steps of the 3D nested structure solar-driven interface steam system are consistent with those in Example 1. Under 1 sun irradiation, the evaporation rate is 4.0156 kg·m -2 ·h -1 The average absorbance in the UV and visible regions is 92%. It can achieve long-term stable brine treatment without any salt deposition and scaling.

[0054] Example 4

[0055] The preparation method of the copper oxide-based photothermal conversion material is basically the same as that in Example 1, except that copper sulfate is replaced by copper nitrate and the length of the hydroxylated multi-walled carbon nanotubes is changed to 50 μm. Under 1 sun irradiation, the evaporation rate is 3.8644 kg·m -2 ·h -1 The average absorbance in the UV and visible regions is 90%. It can achieve long-term stable brine treatment without any salt deposition and scaling.

[0056] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0057] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0058] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a copper oxide-based light-to-heat conversion material, characterized in that: The specific steps include: Step 1: dissolve copper salt in deionized water, add quaternary ammonium salt cationic surfactant, and stir to form a uniform microemulsion; Step 2: Add concentrated ammonia water to the microemulsion synthesized in step 1 by using a constant pressure titration device, perform ultrasonication until the mixture is uniformly mixed, and then heat the mixture in an oil bath and raise the temperature to T1 under stirring; Step 3: injecting a strong alkaline solution into the solution synthesized in step 2 using a peristaltic pump, and continuously stirring until the pH is 9-12 to generate a blue copper hydroxide solution Q1; Step 4: dispersing carbon nanotubes and polyvinyl pyrrolidone in deionized water to form solution Q2, adjusting the type, size and ratio of carbon nanotubes, uniformly mixing solution Q1 and solution Q2, and transferring them to a microwave reactor for microwave hydrothermal reaction, heating the temperature to T2 for continuous reaction, and cooling to room temperature after the reaction is completed; Step 5: Use anhydrous ethanol and deionized water to wash by centrifugation three times, dry at 80°C for 24 hours, and finally obtain the copper oxide-based photothermal conversion material.

2. The method for preparing a copper oxide-based photothermal conversion material according to claim 1, characterized in that: In step 1, the copper salt is one or more of copper nitrate, copper sulfate, copper chloride, copper acetate, copper carbonate, etc.; The quaternary ammonium salt type cationic surfactant is one or more of tetraoctylammonium bromide, methyltriethylammonium chloride, dodecyltrimethylammonium chloride and trimethyldecylammonium bromide.

3. The method for preparing a copper oxide-based photothermal conversion material according to claim 1, characterized in that: In step 1, the copper salt is one or more of copper nitrate, copper sulfate, copper chloride, copper acetate, copper carbonate, etc.; The quaternary ammonium salt type cationic surfactant is one or more of tetraoctylammonium bromide, methyltriethylammonium chloride, dodecyltrimethylammonium chloride and trimethyldecylammonium bromide.

4. The method for preparing a copper oxide-based photothermal conversion material according to claim 1, characterized in that: In step 2, the concentration of the concentrated ammonia water is 25-28wt% and the volume is 2-10ml.

5. The method for preparing a copper oxide-based photothermal conversion material according to claim 1, characterized in that: In step 3, the strong alkaline solution is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, and barium hydroxide; the concentration of the strong alkaline solution is 1-3 mol / L.

6. The method for preparing a copper oxide-based light-to-heat conversion material according to claim 1, characterized in that: In step 4, the mass ratio of the copper salt, carbon nanotubes and polyvinyl pyrrolidone is 5:1:1-15:1:1; The carbon nanotubes are one or more of conventional multi-walled carbon nanotubes, hydroxylated carbon nanotubes, carboxylated carbon nanotubes, and amino carbon nanotubes; the size of the carbon nanotubes is one or more of 0.5-2 μm, 10-30 μm, and 50 μm.

7. The method for preparing a copper oxide-based light-to-heat conversion material according to claim 1, characterized in that: The T1 is 50-80°C, the T2 is 120-240°C, and the reaction time is 0.5-6h.

8. A copper oxide-based light-to-heat conversion material, characterized in that: The method is prepared by any one of claims 1 to 7.

9. The use of a copper oxide-based photothermal conversion material in a 3D nested structure solar-driven interface steam system as claimed in claim 8, characterized in that: The 3D nested structure solar-driven interface steam system includes a water storage unit, a heat insulation unit and a photothermal conversion unit; the heat insulation unit is placed above the water storage unit, and the photothermal conversion unit passes through the heat insulation unit to connect the water body and the air to form a 3D nested structure.

10. The use of a copper oxide-based photothermal conversion material in a 3D nested structure solar-driven interface steam system as claimed in claim 9, characterized in that: The water storage unit is a 50ml beaker filled with simulated seawater; the heat insulation unit is equal to the diameter of the beaker and has a 1×1cm 2 Square through hole, disc-shaped polyethylene foam with a thickness of 1-2 cm; The photothermal conversion unit is to uniformly disperse the copper oxide-based photothermal conversion material in water at a concentration of 30 mg / ml, then inject 3-10 ml into the interior of a foam having a three-dimensional interconnected porous network structure, and dry at 60°C for 10 hours; the foam is one or more of polyurethane foam, melamine foam, polyethylene foam, ethylene-vinyl acetate copolymer foam, and polyimide foam; the foam size is 1×1×3 cm 3 .

Citation Information

Cited By

  • Multifunctional composite coating with high photothermal conversion efficiency and preparation method thereof

    CN121203536A

  • Multifunctional composite coating with high photothermal conversion efficiency and preparation method thereof

    CN121203536B